2020
DOI: 10.24180/ijaws.774969
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Salinity Stress on Chickpea Germination by Salicylic Acid Priming

Abstract: Salinity is a global problem that threatens chickpea (Cicer arietinum L.) cultivation in all stages from germination to maturity. Also, salt-affected areas in the World are increasing by the day. Germination is one of the primary stages affecting plant growth and seed yield. Thus, germination performance of seeds has a vital role in vegetative and productive stages. Seed priming, a cheap and easily applicable technique, improves the germination performance by regulating enzymatic reactions and controlling wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…In a study conducted in Avena sativa L., it was concluded that salinity stress greatly effects parameters such as germination percentage and mean germination time (Kumar et al, 2021). Other similar studies (Melendo & Giménez, 2019;Ceritoğlu & Erman, 2020;Ku-Or et al, 2020;Székely et al, 2021) on this subject also support our results.…”
Section: Discussionsupporting
confidence: 89%
“…In a study conducted in Avena sativa L., it was concluded that salinity stress greatly effects parameters such as germination percentage and mean germination time (Kumar et al, 2021). Other similar studies (Melendo & Giménez, 2019;Ceritoğlu & Erman, 2020;Ku-Or et al, 2020;Székely et al, 2021) on this subject also support our results.…”
Section: Discussionsupporting
confidence: 89%